1α, 25‐dihydroxyvitamin D3 acts via transforming growth factor‐β to up‐regulate expression of immunosuppressive CD73 on human CD4+ Foxp3– T cells. Issue 3 (13th September 2015) - Mann, Elizabeth H.; Chambers, Emma S.; Chen, Yin‐Huai; Richards, David F.; Hawrylowicz, Catherine M.
Summary Vitamin D deficiency is associated with increased incidence and severity of various immune‐mediated diseases. Active vitamin D (1α, 25‐dihydroxyvitamin D3; 1, 25(OH)2D3) up‐regulates CD4+ T‐cell expression of the purine ectonucleotidase CD39, a molecule that is associated with the generation of anti‐inflammatory adenosine. Here we aimed to investigate the direct impact of 1, 25(OH)2D3 on expression of the downstream ecto‐5′‐nucleotidase CD73 by human CD4 T cells, and components of the transforming growth factor‐β (TGF‐β) pathway, which have been implicated in the modulation of CD73 by murine T cells. At 10−8 to 10−7m, 1, 25(OH)2D3 significantly increased expression of CD73 on peripheral human CD4+ T cells. Although 1, 25(OH)2D3 did not affect the mRNA expression of latent TGF‐β1, 1, 25(OH)2D3 did up‐regulate expression of TGF‐β‐associated molecules [latency‐associated peptide (LAP), glycophorin A repetitions predominant (GARP), GP96, neuropilin‐1, thrombospondin‐1 and αv integrin] which is likely to have contributed to the observed enhancement in TGF‐β bioactivity. CD73 was highly co‐expressed with LAP and GARP following 1, 25(OH)2D3 treatment, but unexpectedly, each of these cell surface molecules was expressed primarily on CD4+ Foxp3– T cells, rather than CD4+ Foxp3+ T cells. Notably, neutralization of TGF‐β significantly impaired 1, 25(OH)2D3‐mediated induction of CD73. Collectively, we show that 1, 25(OH)2D3 enhances expression of CD73 on CD4+ Foxp3– T cells in a process that is at least partially TGF‐β‐dependent. These data reveal an additional contributing mechanism by which vitamin D may be protective in immune‐mediated disease.